Weight loss increases circadian gene expression and emotional well-being in individuals with obesity - Grau-del Valle, Carmen; Bosch-Sierra, Neus; Hermo-Argibay, Alberto; López-Domenech, Sandra; Rocha, Milagros; Víctor, Víctor M.; Morillas, Carlos; Rovira-Llopis, Susana; Bañuls, Celia (Frontiers in Nutrition, 2025)
IntroductionObesity is associated with disruptions in circadian rhythms and emotional well-being that can contribute to metabolic and psychological health issues. This study aimed to investigate the effects of weight loss by a dietary intervention on circadian gene expression and emotional state in individuals with obesity.MethodsFifty subjects with obesity followed a dietary intervention for 6 months. Anthropometric and biochemical parameters were assessed. Sleep quality was measured using a sleep questionnaire and Rosemberg Self-Esteem Scale, Beck Depression Inventory and State-Trait Anxiety Inventory (STAI) were used. PBMCs’ RNA was analyzed for circadian-related gene expression.ResultsParticipants lost 11.3% body weight, along with reductions in lipid, carbohydrate metabolism and inflammation markers. Sleep quality improved; as poor sleep frequency was reduced, though sleep duration was similar. Self-esteem did not significantly increase; however, the proportion of participants with high self-esteem rose from 62 to 69% (χ2 = 12.5, p < 0.05). State anxiety decreased (STAI-S, p < 0.01), though trait anxiety remained stable. Several circadian genes were upregulated, including CLOCK, ARNTL, CRY1, DBP, and NR1D1; with associations found between CLOCK and lower state anxiety at baseline, and between CRY2 and higher self-esteem and lower depression at baseline (p < 0.05).ConclusionThe dietary intervention influenced positively the metabolic, psychological, and circadian rhythm marker profile, highlighting potential interconnections between metabolism, circadian gene expression, and mental well-being.Clinical Trial RegistrationIdentifier NCT06279780